Telehealth versus self-directed lifestyle intervention to promote healthy blood pressure: a protocol for a randomised controlled trial - Taher, Mohamed (BMJ Open, 2021)
INTRODUCTION: Weight loss, consumption of a Dietary Approaches to Stop Hypertension dietary pattern, reduced sodium intake and increased physical activity have been shown to lower blood pressure (BP). Use of web-based tools and telehealth to deliver lifestyle counselling could be potentially scalable solutions to improve BP through behavioural modification though limited data exists to support these approaches in clinical practice. METHODS AND ANALYSIS: This randomised controlled trial will compare the efficacy of a telehealth versus self-directed lifestyle intervention in lowering 24-hour SBP in patients with overweight/obesity (body mass index ≥25 kg/m(2)) and 24-hour SBP 120–160 mm Hg. All participants receive personalised recommendations to improve dietary quality based on a web-based Food Frequency Questionnaire, access to an online comprehensive weight management programme and a smartphone dietary app. The telehealth arm additionally includes weekly calls with registered dietitian nutritionists who use motivational interviewing. The primary outcome is change from baseline to 12 weeks in 24-hour SBP. Secondary outcomes include changes from baseline in 24-hour diastolic BP, daytime SBP, nighttime SP, daytime diastolic BP, nighttime diastolic BP, total Healthy Eating Index-2015 score, weight, waist circumference and physical activity. Other prespecified outcomes will include change in individual components of the Healthy Eating Index-2015 score, and satisfaction with the Healthy BP research study measured on a 5-point Likert scale. ETHICS AND DISSEMINATION: The study has been approved by the Geisinger Institutional Review Board. Results will be disseminated through peer-reviewed publications and conference presentations. TRIAL REGISTRATION NUMBER: NCT03700710.